Pengaruh Skeptisme Profesional, Kompetensi, dan Independensi Pada Kualitas Audit - Yoga, Putu Dendy Pratama; Sari Widhiyani, Ni Luh (E-Jurnal Akuntansi, 2019)
This study aims to examine and provide empirical evidence on how the influence of professional skepticism, competence, and independence on audit quality at the BPK Office at least a year experienced in Bali. This study took a sample of all auditors at the BPK Bali Office based on non probability sampling methods with purposive sampling technique and a sample of 40 auditors. Data collection is done by survey method with questionnaire techniques. The analysis technique in this study used multiple linear regression analysis. The results of the analysis show that professional skepticism, competence and independence have a positive effect on audit quality. This shows that the higher the professional skepticism, competence, and independence possessed by the auditor, the better the quality of the audit produced. Keywords: Professional skepticism, competence, independence and audit quality.